The Project Based Learning Model on Students' Critical Thinking Skills - Indah Pratiwi (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
This research is motivated by the lack of students' critical thinking skills, students tend to be passive in the learning process, and teachers are less precise in implementing learning models that can train students' critical thinking skills. This research aims to determine students' critical thinking skills. This research method is a quantitative research method. The population is class IV students at SD Negeri 173642 Hasahatan which consists of one class. Sampling was carried out with saturated samples. The independent variable is the Project Based Learning learning model, the dependent variable is students' critical thinking skills. Hypothesis testing uses Paired sample T-Test which is preceded by a validity test and a reliability test. The results of this research using hypothesis testing obtained a significance value of .000. Means 0.000 < 0.05, then Ha is accepted. It can be concluded that there is an influence of the application of the Project Based Learning model on the Critical Thinking Skills of Class IV Students at SD Negeri 173642 Hasahatan".